Problems of Border Regions in Ensuring Legal Certainty Invest in Indonesia - Rieta Lieke Lontoh (Susbtantive Justice International Journal of Law, 2019)
The mandate of Article 33 of the 1945 Constitution of the Republic of Indonesia maximizes all elements of development as an effort to realize the people's prosperity through the development of law in the field of investment in the perspective of regional autonomy in the border regions of the Republic of Indonesia. Border areas are a problem because legal certainty for investors has yet to find a meeting point for investment, especially in border areas, so it seems that government responsibilities are still minimal in efforts to equalize the welfare of its people. Normative juridical research methods using secondary legal materials produce a coherent legal science research in finding the truth, and the results of this study suggest that legal certainty does not accommodate the interests of development in border areas, causing a chain problem and an investment climate improvement is based on the fact that the lack the interest of foreign investors in Indonesia is caused by various obstacles, which in turn hinder the business of investors or cause the transfer of business to other countries. The author concludes to overcome economic problems, especially in investing, the government takes steps to encourage the competitiveness of national industries, through deregulation, bureaucratization, and law enforcement and business certainty. Therefore, through this paper, it is necessary to reform the legal rules by preparing regional regulations, especially in North Sulawesi relating to investment management in the border region, as a sample of study material that can provide legal certainty and protection for investors throughout Indonesia